Peran modeling dan scaffolding guru dalam internalisasi nilai kejujuran pada peserta didik kelas rendah - Ana Riyanti; Mochamad Widjanarko; Indah Lestari (Universitas Sarjanawiyata Tamansiswa, 2026)
This study aims to reveal the role of teachers as models and mentors (modeling and scaffolding) in the internalization of honesty values among lower-grade elementary school students. This phenomenon is crucial because the low consistency of students’ honest behavior requires a character education approach grounded in exemplarity and moral experience. The study employs a qualitative approach with a phenomenological method, focusing on teachers’ lived experiences cultivating honesty in the classroom. Data were collected through semi-structured interviews, participatory observation, and reflective documentation involving six lower-grade teachers from three public elementary schools in Toroh District, Grobogan Regency. Data were analyzed using Interpretative Phenomenological Analysis (IPA) through open, thematic, and reflective coding. The findings reveal four central themes: (1) honesty as a teacher’s moral identity, (2) modeling as a value role model, (3) moral scaffolding as a process of value internalization, and (4) school culture as a character ecosystem. Teachers act as moral agents who instill honesty through exemplarity and social interaction. The success of character education depends on the consistency of teachers’ behavior and the support of the school’s moral culture. This study emphasizes the importance of reflective training for teachers and collaboration between schools and families in fostering sustainable honesty values.